Fourth Annual Report of Severn Wildfowl Trust, 1950-1951 - Anonymous, Anonymous (Wildfowl, 1951)
No abstract available. Contents include the following: WILD GEESE: Total Numbers, Pink-footed Goose, Bean Goose, Counts, European White-fronted Goose, Greenland White-fronted Goose, Lesser White-fronted Goose, Barnacle Goose, Aggressive Behaviour in the White-fronted Goose, Disturbance by Aircraft, Marking of Wild Geese: Pink-footed Geese, Recovery; Notes on Colour Marking of Geese: Rejected Methods, Use of Dyes, Preparation of Solutions, Application, Visibility of Colours, Effects of Dyeing on Birds; WILD DUCKS: The Decoy: The Lead, The Catch, Progress of Total Catch, Catch and Ringing Figures, Methods of Capture in Decoy; Status of Ducks: Common Shelduck, Pintail, Teal, Mallard, Gadwall, Wigeon, Garganey, Shoveler, Pochard, Tufted Duck; RINGING AND RECOVERIES: Bird Ringing, Recoveries, Details of Recoveries; BIRDS (Other than Anatidae) RECORDED AT THE NEW GROUNDS; WATERFOWL COLLECTION: New Species, Important Additions, List of Birds in the Collection, The Breeding Season, Hatching and Rearing, Pathology, Treatment, Causes of Death, The Scientific Value of a Group Collection of Live Animals, Preening Studies, Sweden 1950; GENERAL ACTIVITIES AND ADMINISTRATION: Visitors, Beatrice, Finance, Bulletins, Director’s Lecture, Wants; FOURTH ANNUAL GENERAL MEETING: Minutes, Income and Expenditure Account, Balance Sheet, Annual Dinner, Obituary, Membership; LIST OF MEMBERS; THE SWANS, GEESE AND DUCKS OF THE BRITISH ISLES: Plate V–Shelducks; Plate VI–Dabbling Ducks; Plate VII–Dabbling Ducks; Plate VIII–Dabbling Ducks.